Electrical conductivity behaviour of the solid solution Ba1-xLaxTi1-xCoxO3 - Kumar D.; Prasad Ch.D.; Parkash O. (My University, 2025)
The d.c. resistivity and Seebeck coefficient were measured as a function of temperature in the Ba1-xLaxTi1-xCoxO3 system for samples with x ≤ 0.50 in the 300-800 K temperature range. The a.c. conductivity was measured as a function of temperature and frequency for samples with x ≤ 0.20. The a.c. conductivity data indicate that conduction occurs among localized sites giving rise to Debye-type loss at low temperatures. The results of d.c. conductivity measurements combined with a.c. conductivity data at high temperatures indicate that electrical transport occurs by the excitation of charge carriers near the valence band edge and hopping as small polarons at energies close to it. © 1990.